KEMAMPUAN BEBAN PAJAK TANGGUHAN DALAM MENDETEKSI MANAJEMEN LABA - Yulianti, Yulianti (UI Scholars Hub, 2005)
The purpose of this study is to investigate whether the Deferred Tax Expenses analysis can be employed to detect earnings management in Indonesian Capital Market. This study also compares the deferred tax expenses method and the accrual method as the proxy of Earnings Management. This study finds that deferred tax expenses and the accrual measures (using Total Accruals model, Modified Jones Model and Forward Looking Model) have positive and significant impacts on the probability of earnings management to avoid losses. It means that the bigger the value of Accrual and Deferred Tax Expenses the bigger the probability of earnings management practices. Of the three models used, the deferred Jax expenses variable has similar significances compared to total accrual model and higher significances compared to the discretionary accrual models. This shown that deferred tax expenses can be used as an alternative to Accrual Models in explaining the earnings management phenomena around the earnings threshold. In the additional study, we find that factors affected earnings management can't explain the variation of Deferred Tax Expenses. Meanwhile it can be used to explain the three-accrual models significantly. This finding suggests that the use of deferred tax expenses as a proxy in earnings management is still in doubt.